Research studies on human cognitive ability. (15th May 2019) - Sinha, G.R.; Raju, K. Srujan; Patra, Raj Kumar; Aye, Daw Win; Khin, Daw Thuzar
Research on cognitive ability of human brain can be seen now in literature that substantiates research scope and future directions in the field of human brain and its cognitive ability. This paper studies on research articles and work that highlighted various studies; surveys; and comparison on human brain research and its impact on cognitive ability for various artificial intelligence (AI) based applications. The research studies result several important questions on machine learning and impact of cognitive ability.